2013
DOI: 10.1673/031.013.10201
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Distribution and Niche Divergence of Two Stinkbugs,Parastrachia japonensisandParastrachia nagaensis

Abstract: Parastrachiidae is a small stinkbug family containing only one genus and two species, Parastrachia japonensis (Scott) (Hemiptera: Heteroptera: Pentatomoidea) and Parastrachia nagaensis Distant. The geographic distribution of the genus has been poorly studied. Niche conservatism refers to that idea that closely related species are more ecologically similar than would be expected, whereas niche divergence predicts they occupy distinct niche spaces. The existence of only two species within one genus suggests nich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 71 publications
(110 reference statements)
0
7
0
Order By: Relevance
“…Environmental niche modelling (ENM) uses widely available environmental and georeferenced distribution data [ 19 ], and it has proven useful as a tool to help estimate niche conservatism or niche divergence among related taxa [ 20 , 21 , 22 , 23 , 24 , 25 ]. Several studies have shown that degrees of ecological difference constitute important evidence in distinguishing species [ 4 , 8 , 24 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Environmental niche modelling (ENM) uses widely available environmental and georeferenced distribution data [ 19 ], and it has proven useful as a tool to help estimate niche conservatism or niche divergence among related taxa [ 20 , 21 , 22 , 23 , 24 , 25 ]. Several studies have shown that degrees of ecological difference constitute important evidence in distinguishing species [ 4 , 8 , 24 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has clearly demonstrated the role of ecology in the speciation process [7,31,37,54,55]. It is clear that a species' range is influenced by its ecological niche [56], which is defined by the combination of environmental conditions and resources that are necessary for an organism to maintain a viable population [57].…”
Section: Discussionmentioning
confidence: 99%
“…large-scale climatic changes in geological history), they have three possible solutions: evolve, change range or become extinct [1]. There are a large number of examples showing insect species that have changed range and/or evolved as a response to repeated isolation during glaciation-interglaciation cycles [2][3][4][5][6][7]. In the Western Palearctic, there are multiple glacial refugia: southern Europe (Iberian, Apennine and Balkan peninsulas), the Anatolian Peninsula and southern Caucasus [2,8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, ENM has been increasingly used for characterizing the ecological requirements of species (e.g., Owens et al 2012), conservation priority setting (e.g. Irfan-Ullah et al 2006) and other aspects of ecology and evolution Zhu et al 2012Zhu et al , 2013.…”
Section: Introductionmentioning
confidence: 99%